TAFSIR QUR’AN INDONESIA TENTANG AGAMA-AGAMA: Telaah Kitab “Al-Quran dan Tafsirnya” dan Kitab “Tafsir al-Mishbah” - Syamsul Hidayat (Universitas Muhammadiyah Surakarta, 2016)
This study departs from the questions of how the paradigm of the study of religions according to the Koran, which include: the vision of the Quran about the meaning and concept of religion, the Koran's vision about the meaning and scope of the study of religions, Quran vision methods and approach, and purpose in religious studies. Methodologically, this study focuses its study on the book of Tafsir al-Misbah M. Quraish Shihab's work, and al-Karim wa Quranul Tafsiruhu Ministry of Religious Affairs team works primarily related verses above problems, by using mawdû'i approach. After going through the process of data collection and analysis, some conclusions can be drawn se¬bagai the following: (1) The concept of religion in the sight of the Koran there are two meanings, as the revelation of God's religion is absolute and sacred, and aga¬ma as the process and outcome of human understanding the revelation of God, which is profane and relative, (2) Al-Quran shows that the study of religion, both in the sense and meaning ke¬dua first, the principle of plurality. The existence of truth claims, is at the basic ideas and the religious substance of the cored al-Islam or al-istislam, and tawhid. The study of religions in view of the Quran in addition to nature of science, as well as socio-ethical and theological. Kajian ini berangkat dari pertanyaan bagaimanakah paradigma studi agama-agama menurut Al-Quran, yang meliputi: visi Al-Quran tentang makna dan konsep agama, visi Al-Quran tentang pengertian dan ruang lingkup studi agama-agama, visi Al-Quran tentang metode dan pendekatan, serta tujuan dalam studi agama. Secara metodologis, kajian ini memfokuskan kajiannya kepada kitab Tafsir al-Misbah karya M. Quraish Shihab, dan Al-Quranul Karim wa Tafsiruhu karya Tim Kementerian Agama RI terutama ayat-ayat yang berkaitan permasalahan di atas, dengan menggunakan pendekatan mawdû'i. Setelah melalui proses pengumpulan data dan analisis, dapat diambil beberapa kesimpulan sebagai berikut: (1) Konsep agama dalam pandangan Al-Quran ada dua makna, agama sebagai wahyu Allah yang mutlak dan sakral, dan agama sebagai proses dan hasil pemahaman manusia terhadap wahyu Allah, yang bersifat profan dan relatif, (2) Al-Quran menunjukkan bahwa kajian terhadap agama, baik dalam arti yang pertama maupun makna yang kedua, dengan prinsip pluralitas. Adanya klaim kebenaran, berada pada wilayah ide-ide dasar dan substansi keberagamaan yang berintikan pada al-islâm atau al-istislâm, dan tawhid. Studi agama-agama dalam pandangan Al-Quran disamping bersifat keilmuan, juga sosial etis dan teologis.